On the analysis of building a public information platform based on e-Commerce for coal logistics - Zeguo Qiu (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: Putting forward the concept and features of the public information platform for coal logistics based on electronic commerce, as well as the requirements of upper and lower intersections of the coal supply chain. Meanwhile, this paper will also probe into the current condition of statistics management in coal logistics, and then discuss how to build a public information platform based on electronic commerce for coal logistics. Design/methodology/approach: According to the further exploring the concepts and relevant characteristics and the development of coal logistics and supply chain management in China of the current period. Findings/ Practical implications: An advanced public information platform for coal logistics utilizes to best advantage modern information technologies and managerial concepts in the operation of coal logistics, such as e-commerce, e-information, supply chain management, etc. This not only stimulates efficient integration of business flow, information flow, logistics and capital flow of the coal industry, brings about in-depth integration of the logistics resources of the coal industry, but also greatly improves the efficiency of the operation of coal logistics, reduces the cost of coal logistics, and enhances the overall competitiveness of upstream and downstream companies along the coal supply chain. Research limitations/implications: Although the coal logistics public information platform has been applied in some enterprises in China, not yet in a broader range of applications, which need the joint efforts of all parties. Originality/value: Fitted to the e-commerce era, the Public Information Platform for Coal Logistics envisioned in this article is highly feasible and worthy of reference to relevant institutions.
Keywords: 650; coal logistics; supply chain management; electronic commerce; public information platform